Nanomaterial‐assisted oncolytic bacteria in solid tumor diagnosis and therapeutics - Xiangdi Zeng; Qi Chen; Tingtao Chen (Wiley, 2024)
Abstract Cancer presents a formidable challenge in modern medicine due to the intratumoral heterogeneity and the dynamic microenvironmental niche. Natural or genetically engineered oncolytic bacteria have always been hailed by scientists for their intrinsic tumor‐targeting and oncolytic capacities. However, the immunogenicity and low toxicity inevitably constrain their application in clinical practice. When nanomaterials, characterized by distinctive physicochemical properties, are integrated with oncolytic bacteria, they achieve mutually complementary advantages and construct efficient and safe nanobiohybrids. In this review, we initially analyze the merits and drawbacks of conventional tumor therapeutic approaches, followed by a detailed examination of the precise oncolysis mechanisms employed by oncolytic bacteria. Subsequently, we focus on harnessing nanomaterial‐assisted oncolytic bacteria (NAOB) to augment the effectiveness of tumor therapy and utilizing them as nanotheranostic agents for imaging‐guided tumor treatment. Finally, by summarizing and analyzing the current deficiencies of NAOB, this review provides some innovative directions for developing nanobiohybrids, intending to infuse novel research concepts into the realm of solid tumor therapy.